Numerical Simulation of Simultaneous Electrostatic Precipitation and Trace Gas Adsorption: Electrohydrodynamic Effects - Clack, Herek L. (Frontiers in Energy Research, 2017)
Quasi-1-D analytical expressions for predicting the performance of electrostatic precipitators (ESPs) were developed from first principles decades ago and still find use in the present day, although significant simplifying assumptions are employed and manufacturers and operators still incorporate adjustable parameters to match field data. ESPs tasked with simultaneous particulate removal and trace gas-phase pollutant removal, however, represent a significant departure from their original operational mission. The present study extends our previous study of such ESP operations and uses the same computational platform to examine details of the multi-phase flow phenomena within ESPs as a function of the strength of the electro-hydrodynamic (EHD) fluid flow phenomena that can occur under high current density operating conditions or low fluid velocities. In particular, the results show good agreement between numerical simulation and classical ESP performance prediction equations at low current densities, and increasing divergence in predicted performance at higher current densities. Under the influence of EHD phenomena, the acceleration of the fluid by electric body forces effectively increases average fluid velocities through the ESP channel with the expected reduction in PM removal efficiency. The impact on trace pollutant is mixed, with both promotion and inhibition mechanisms associated with EHD phenomena identified.